Bobos in paradise the new upper class and how they got there - Brooks, David (Simon & Schuster, 2000)
In this work of "comic sociology," David Brooks coins a new word, Bobo, to describe today's upper class--those who have wed the bourgeois world of capitalist enterprise to the hippie values of the bohemian counterculture. You know, those visionary software companies where people come to work wearing hiking boots and glacier glasses and seek oneness with the rhythms of nature. Their hybrid lifestyle is the atmosphere we breathe--it defines our age--and in this witty and serious look at the cultural consequences of the information age, Brooks has defined a new generation.--From publisher description.